Hemodynamic Conundrum of Thyroid Storm-Induced Acute Heart Failure: Challenging Case in a Remote Area - Dya Pratama Andryan; Susandy Oetama; Oktavia Lilyasari (Jurnal Kardiologi Indonesia, 2026)
In “Hemodynamic Conundrum of Thyroid Storm-Induced Acute Heart Failure: Challenging Case in a Remote Area” (Indonesian Journal of Cardiology, 46(2), 89-95. https://doi.org/10.30701/ijc.1701), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1701. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1701